Cruzipain Induces Both Mucosal and Systemic Protection against Trypanosoma cruzi in Mice - Schnapp, Anita R. (American Society for Microbiology, 2002)
Cruzipain, the major cysteinyl proteinase of Trypanosoma cruzi, is expressed by all developmental forms and strains of the parasite and stimulates potent humoral and cellular immune responses during infection in both humans and mice. This information suggested that cruzipain could be used to develop an effective T. cruzi vaccine. To study whether cruzipain-specific T cells could inhibit T. cruzi intracellular replication, we generated cruzipain-reactive CD4(+) Th1 cell lines. These T cells produced large amounts of gamma interferon when cocultured with infected macrophages, resulting in NO production and decreased intracellular parasite replication. To study the protective effects in vivo of cruzipain-specific Th1 responses against systemic T. cruzi challenges, we immunized mice with recombinant cruzipain plus interleukin 12 (IL-12) and a neutralizing anti-IL-4 MAb. These immunized mice developed potent cruzipain-specific memory Th1 cell responses and were significantly protected against normally lethal systemic T. cruzi challenges. Although cruzipain-specific Th1 responses were associated with T. cruzi protective immunity in vitro and in vivo, adoptive transfer of cruzipain-specific Th1 cells alone did not protect BALB/c histocompatible mice, indicating that additional immune mechanisms are important for cruzipain-specific immunity. To study whether cruzipain could induce mucosal immune responses relevant for vaccine development, we prepared recombinant attenuated Salmonella enterica serovar Typhimurium vaccines expressing cruzipain. BALB/c mice immunized with salmonella expressing cruzipain were significantly protected against T. cruzi mucosal infection. Overall, these data indicate that cruzipain is an important T. cruzi vaccine candidate and that protective T. cruzi vaccines will need to induce more than CD4(+) Th1 cells alone.